Measuring herd behavior: properties and pitfalls - Lee Woojoo; Ahn Jae Youn (Dependence Modeling, 2017)
Herd behavior is an important economic phenomenon, especially in the context of the recent financial crises. Prior studies propose several measures to quantify herd behavior. In this paper, we show that these measures reflect different perspectives on this behavior, and hence, their interpretation requires great care. Taking a critical attitude toward existing herd behavior measures, we study their properties and pitfalls in detail.